Otto Isakower and Salomea Isakower papers - Isakower, Otto, 1899-1972.; Isakower, Salomea, 1888-
Correspondence, writings, biographical data, and other papers pertaining to the work of Otto Isakower and to the history of psychoanalysis during his lifetime. Includes minutes (1923-1924) from meetings of the Vienna Psychoanalytic Society (Wiener Psychoanalytische Vereinigung), papers relating to the Isakowers' immigration and resettlement, a patient case file from the Vienna Allgemeines Krankenhaus, and data on dreams. Correspondents include Paul Federn, Anna Freud, Ernest Jones, Bertram David Lewin, and Herman Nunberg. Also includes photocopies of Sigmund Freud letters to Carl Koller (1880-1887) and to Albrecht Schaeffer (1939).
Library of Congress Prints and Photographs Division.
Psychoanalyst and author. Salomea Isakower (born Salomea Rettych in 1888), a physician, formerly Mrs. Felix Gutman, married Otto Isakower in 1938.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
The 1984 gift was originally processed as part of the Sigmund Freud Papers from which it was separated in 1990.
Keywords: Federn, Paul -- Correspondence; Freud, Anna, -- 1895-1982 -- Correspondence; Freud, Sigmund, -- 1856-1939 -- Correspondence; Jones, Ernest, -- 1879-1958 -- Correspondence; Koller, Carl, -- 1857-1944 -- Correspondence; Lewin, Bertram David, -- 1896- -- Correspondence; Nunberg, Herman, -- 1884-1970 -- Correspondence; Schaeffer, Albrecht, -- 1885-1950 -- Correspondence; Allgemeines Krankenhaus (Vienna, Austria); Wiener Psychoanalytische Vereinigung; Dreams; Psychoanalysis; Psychoanalysis -- Austria -- Societies, etc; Authors; Physicians; Psychoanalysts